Toured to death - Conrad, Hy (Conrad, Hy. Amy's Travel mystery., 2015)
"While Fanny takes care of the business end of Amy's Travel in New York City, Amy is traipsing around Monte Carlo, managing their first mystery-themed excursion, a road rally in which guests compete to solve a fictional murder along the way. Amy still has reservations about partnering up with her mother. But both women, having lost the men in their lives, need a fresh beginning. The trip starts off without a hitch. Clues quickly mount, the competition is lively and just when the suspense is peaking, the writer they hired to script their made-up mystery is found murdered in his New York apartment."--Jacket.